Using the Theoretical Domains Framework to investigate clinicians' behavioural determinants of antimicrobial prescribing in Qatar. (26th March 2021) - Talkhan, H; Stewart, D; McIntosh, T; Ziglam, H; Abdulrouf, P V; Al-Hail, M; Diab, M; Cunningham, S
Abstract: Introduction: A recent systematic review by Talkhan et al demonstrated the need for theoretically based behaviour change interventions in this area. [1] For development of such complex interventions, emphasis should be placed on using theory to systematically identify behavioural determinants of antimicrobial prescribing. Aim: To identify and quantify clinicians' behavioural determinants of antimicrobial prescribing in Qatar. Methods: This cross-sectional survey is part of a multi-phase explanatory, sequential mixed methods PhD project in Qatar. Questionnaires were distributed (online and paper based) to all doctors (~4, 000) and pharmacists (~400) within Hamad Medical Corporation (HMC, the main healthcare provider). The questionnaire was developed with reference to the Determinants of Implementation Behaviour Questionnaire (a generic questionnaire derived from the 14 theoretical domains of the Theoretical Domains Framework, TDF). [2] Each item was presented as a 5-point Likert scale (scored 5=Strongly agree to 1=Strongly disagree). Personal and practice demographics were also collected for data contextualisation. The draft questionnaire was reviewed for face/content validity by an expert panel of six researchers in Qatar and the UK with experience in the use of the TDF, followed by 'Think aloud' testing and piloting. Analysis investigated the behavioural determinants and influential factors through descriptive, principal component analysis (PCA) and inferential analysis. Ethics approval was granted from a UK university and HMC. Results: In total, 535 responses were received, 339 (63.4%) from doctors and 196 (36.6%) from pharmacists. Respondents were predominantly male, 346 (64.7%). Just over half (n=285, 53.3%) had ≤ 5 years' experience as health professionals. PCA showed a three component (C) solution with components incorporating a number of questionnaire items labelled: 'Guidelines compliance' (C1 with 8 items), 'Influences on prescribing' (C2 with 7 items) and 'Self-efficacy' (C3 with 5 items) in prescribing/recommendation activity. A scale score for each respondent was calculated through summation of Likert scores for the relevant questionnaire items within each component. These scales had high internal reliability (Cronbach's alpha all >0.7) showing consistency in response between component items indicating statistical appropriateness for developing scales. The median score (possible scale range, midpoint) for each scale was C1, 32 (8 to 40, 24), C2, 26 (7 to 35, 21) and C3, 20, (5 to 25, 15). By way of example Table 1 shows levels of agreement for items in C2. This shows lower levels of agreement than C1 scale with the median scale score (26) closer to the midpoint (21) indicating that respondents had less positive views. Inferential analysis using these scale scores and free text analysis is in progress. Conclusion: A theoretical basis was used throughout providing insights to behavioural determinants for the development of a theory-based behaviour change intervention. Preliminary results suggest that social influences, staff development and quality monitoring may be useful targets for behaviour change interventions to improve antimicrobial prescribing practice. Limitations include potential social desirability bias and focus on one healthcare organisation/country in the Middle East which may limit generalisability of findings. More in-depth exploration is required to select and test appropriate linked theory-based behaviour change techniques. References: 1. Talkhan H, Stewart D, McIntosh T, Ziglam H Palli Valapila, A; Moza Sulaiman H, Diab M, Cunningham S. The use of theory in the development and evalu​ation of behaviour change interventions to improve antimicrobial prescribing: a systematic review. J Antimicrob Chemother. 2020;75(9):2394–2410, Available from https://doi.org/10.1093/jac/dkaa154 [Accessed 12 Oct 2020]. 2. Huijg JM, Gebhardt WA, Dusseldorp E, Verheijden MW, van der Zouwe N, Middelkoop BJ, Crone MR. Measuring determinants of implementation behaviour: psychometric properties of a questionnaire based on the Theoretical Domains Framework. Implement. Sci. 2014;9(1):33.